АКТУАЛЬНІСТЬ РЕНОВАЦІЇ ПАРКІВ МІСЬКОГО ПРОСТОРУ НА ПРИКЛАДІ ГІДРОПАРКУ ЛУЗАНІВКА В М. ОДЕСА - Сторожук, Світлана; Інякіна, Анастасія; Мустяц, Юлія (Містобудування та територіальне планування, 2022)
The article discusses the possibility of renovating park areas in order to create public spaces, taking into account all the existing problems of this area, the wishes of residents and the foundations of sustainable development. The main objectives of the study are: to analyze the environmental, natural and anthropogenic factors of mutual influence, as well as the interaction of the relevant systems in areas with urban development, its slow development, and especially during reconstruction and renovation; to substantiate the problem of renovation of urban spaces in the ratio of city-forming zones (industrial, rural and recreational); trace the development of park areas in connection with the development of the city and determine ways to solve the problems of renovation of urban spaces; present a comprehensive architectural concept of linking park and recreation areas and development of the coast of the Odessa Bay. After analyzing the history of the emergence and development of parks in Ukraine, first of all, the historical features of the territory where the hydropark "Luzanovka" is located, the importance of this park area for various factors (environmental, social, urban planning, etc.) is revealed. The introduction of new functions in the territories of historical parks, the competent development of an urban planning structure through the renovation and rehabilitation of the territory will lead to an influx of funds and investors, and will make it possible to reproduce and maintain parks at a new historical stage. The article presents the features of the design and renovation of parks, identifies trends in the further development of the territory, presents social and environmental effects, and provides an example of a project for the renovation of the Luzanovka hydropark.